MICROBIAL QUALITY OF LIQUID HERBAL PRODUCTS HAWKED WITHIN KADUNA METROPOLIS - Aliyu, Aishatu Mohammed; Abdulhamid, Ibrahim R.; Aliyu, Yakasai M. (FUDMA JOURNAL OF SCIENCES, 2025)
Herbal medicine refers to the use of plants for the treatment of illness. The aim of this study was to assess the microbial quality of liquid herbal products hawked within Kaduna metropolis. A total of 28 herbal samples were collected from different markets and were analyzed for the presence of bacteria and fungi using standard method of spread plate method. The isolated bacteria were further tested for antibacterial susceptibility to commonly used antibiotics using disc diffusion technique. The result showed Kawo market had the lowest bacterial count of 3.17±2.16 x106, while Unguwan rimi market had the highest bacterial count of 4.45±2.49 x106. Unguwan Rimi market had the lowest fungal count of 2.27±1.76x103, while Sabo market had the highest fungal count of 3.18±1.82x103. Seventeen 17(60.71%) of the products were contaminated with different bacterial species including Escherichia coli, Salmonella spp, Staphylococcus aureus and Pseudomonas sp with percentage occurrence of 100%, 35.29%, 76.47 and 58.82% respectively. Fifteen 15(53.57) of the products were contaminated with different fungal species including Aspergillus niger, A. flavus, A fumigatus, Mucor sp and Rhizopus sp with percentage occurrence of 20.0%, 26.67%, 13.33%, 20.0% and 13.33% respectively. All the bacterial isolates were resistant to ampicillin and ceftazidine, 59% of E. coli were susceptible to gentamicin and nitrrofurantoin. Staphylococcus aureus had a 100% susceptibility to ciprofloxacin and ofloxacin. Eighty (80%) of Pseudomonas sp were susceptible to gentamicin, while 83% of Salmonella spp were susceptible to gentamicin.
Keywords: Bacteria; Fungi; Herbal medicine; Market; Susceptibility